Osobennosti kharaktera studentov - legkoatletov i basketbolistov - Malinauskas, R. K. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
In the sports literature on psychology there is no uniform opinion on distinctions between character traits of the sportsmen of various kinds of sports (in this article - track&field athletes and basketball players). With use of the Roter's technique there was established, that the representatives of track&field athletics as are emotionally astable, as well as all people. The results of one interesting research became object of discussion concerning the probable pathology in a compelled runner. Such runners were capable to suppress the anger, to operate themselves and even to deny the real or imaginary own weaknesses. It was revealed, that the compulsory running occupations have disguised their depressive condition. "Compelled athlete - typical oppressed man able to overcome depression by running". Therefore it is necessary to determine, whether the same character trait is peculiar to basketball players (representatives of sports games).